PEMBERDAYAAN MASYARAKAT KOMUNITAS UMKM KACANG ASIN DI KECAMATAN SUSUKAN, KABUPATEN BANJARNEGARA MELALUI PEMBUATAN MESIN SANGRAI KACANG DENGAN PENGATURAN KECEPATAN DAN INDIKATOR SUHU - Puspita, Rina; Haris Kuspranoto, Abdul; Amalya, Choiry; Ulin Nuha ABA, Muhammad; Febrianto, Agil (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2025)
The empowerment of salted peanut MSMEs in Susukan Subdistrict, Banjarnegara Regency, was carried out by implementing a peanut roasting machine equipped with advanced technology, including automatic temperature control and an even stirring system. This machine has a capacity of 25 kg and 10 kg, which is designed to improve efficiency, quality consistency, and the production capacity of local MSMEs. Previously, the roasting process was done manually with strict monitoring of temperature and stirring, which affected quality stability and took a long time. The implementation of this machine reduces dependence on individual skills and provides more precise control over roasting temperature and time, which in turn produces salted peanuts with more consistent quality and reduces losses due to defective products. In addition to increasing production efficiency, this machine also opens up opportunities for local artisans to be more involved in the production process without having to possess high skills. This program not only increases the productivity of MSMEs but also creates new jobs, provides technical skills training, and improves the welfare of the local community. Grant support from the Ministry of Education, Technology, and Innovation (Kemendikstaintek) through the BEM Berdampak scheme facilitated the smooth implementation of this machine, enabling the project to run successfully. The application of this technology has had a significant social and economic impact on salted peanut MSMEs and serves as an example of a technology-based economic empowerment model that can be applied in other regions to encourage more inclusive and sustainable local economic growth.